Role of Sex Hormones in the Control of Vegetative and Metabolic Functions of Middle-Aged Women - Monda, Vincenzo; Salerno, Monica; Fiorenzo, Moscatelli; Villano, Ines; Viggiano, Andrea; Sessa, Francesco; Triggiani, Antonio I.; Cibelli, Giuseppe; Valenzano, Anna; Marsala, Gabriella; Zammit, Christian; Ruberto, Maria; et al. (Frontiers in Physiology, 2017)
Aims: In women’s life, menopause is characterized by significant physiological changes often associated with an increase in body weight and obesity-related diseases. Many studies have been carried out to determine interdependencies of estrogen depletion, aging, and resting energy expenditure (REE) decline in menopause-related obesity. Methodology: In this study, we measured the body composition, the REE, the oxidative stress, the food intake, and the activity of the autonomic nervous system of three groups: pre-menopause women (n=50), post-menopause women following hormone-replacement therapy (HRT; n=50), and post-menopause women not following HRT (n=50). Results: In post-menopause women with HRT a significant increase was found in: 1) the sympathetic activity, measured by the power spectral analysis of the heart rate variability; 2) REE, measured by indirect calorimetry; 3) oxidative stress, measured by FRAS 4 compared to the value of the other two, while fat mass, measured by BIA, was reduced in favor of a recovery of free fat mass. Conclusion: The study highlights the importance of the HRT-related physiological changes that influence body weight in menopause women.